2008
DOI: 10.1002/elsc.200700059
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Membrane Proteins: the Case of G‐Protein‐Coupled Receptors

Abstract: G-protein-coupled receptors are integral membrane proteins which constitute the largest family of signal transduction molecules participating in the majority of normal physiological processes. G-protein-coupled receptors are responsible for the control of enzyme activity, ion channels and vesicle transport, and they respond to a wide variety of stimuli, like signals involved in sensory systems such as vision, taste and olfaction, but also to a diverse set of chemical signals such as lipids, hormones, neurotran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…These heuristics implicitly assume that molecular chemistry is the most, if not the only, important variable in selecting a micellar system to retain the in vitro stability of membrane proteins. This typically leads to strategies in which pure micelles of a particularly mild surfactant are used as a first attempt (e.g., dodecyl maltoside), and the micellar system is fine-tuned through the use of other detergents or additives until a suitable system is found for the protein and biophysical method of interest (16,18). Such trial-and-error methodology is time-consuming and resource-intensive, especially considering the low yields that are typically achieved for expression and purification of most membrane proteins, and does not lead to information that is readily translatable across different systems.…”
Section: Introductionmentioning
confidence: 99%
“…These heuristics implicitly assume that molecular chemistry is the most, if not the only, important variable in selecting a micellar system to retain the in vitro stability of membrane proteins. This typically leads to strategies in which pure micelles of a particularly mild surfactant are used as a first attempt (e.g., dodecyl maltoside), and the micellar system is fine-tuned through the use of other detergents or additives until a suitable system is found for the protein and biophysical method of interest (16,18). Such trial-and-error methodology is time-consuming and resource-intensive, especially considering the low yields that are typically achieved for expression and purification of most membrane proteins, and does not lead to information that is readily translatable across different systems.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the molecular interactions that stabilize or destabilize membrane proteins is essential to our understanding of their function (11,22,23). High stability of GPCRs in solution is desirable for biotechnological applications (24), biochemical assays, and structural studies. It has been previously shown that inorganic salts play a key role in the stability of proteins (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), and whereas a large number of studies are available for globular proteins, less information is available in the case of membrane proteins.…”
Section: Introductionmentioning
confidence: 99%